Interplay between turbulence, neoclassical and zonal flows during the transition from low to high confinement mode at ASDEX Upgrade. (17th October 2016) - Cavedon, M.; Pütterich, T.; Viezzer, E.; Birkenmeier, G.; Happel, T.; Laggner, F. M.; Manz, P.; Ryter, F.; Stroth, U.
Abstract: The spatio-temporal interplay between turbulence, mean and zonal flows has been investigated at the L–H and H–L transitions in the edge region of the ASDEX Upgrade tokamak. Close to both transitions, an intermediate phase (I-phase) characterized by 'limit cycle like oscillations' (LCOs) is observed in which periodic bursts of turbulence correlate with E × B flow reduction and relaxation of gradients. During the I-phase, the E × B velocity is dominated by the mean flows indicating that turbulence driven flows are small. Periodic dithers between L-mode and the phases with LCOs are also observed just before the H-mode onset where the edge density and temperature profile gradients evolve on similar timescale as the flows. Thus connection between mean and E × B flows holds during the all evolution from L-mode to H-mode demonstrating the fundamental role of the neoclassical flows in the L–H transition physics.